The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/gb-2014-15-3-r51
|View full text |Cite
|
Sign up to set email alerts
|

Imperfect centered miRNA binding sites are common and can mediate repression of target mRNAs

Abstract: BackgroundMicroRNAs (miRNAs) bind to mRNAs and target them for translational inhibition or transcriptional degradation. It is thought that most miRNA-mRNA interactions involve the seed region at the 5′ end of the miRNA. The importance of seed sites is supported by experimental evidence, although there is growing interest in interactions mediated by the central region of the miRNA, termed centered sites. To investigate the prevalence of these interactions, we apply a biotin pull-down method to determine the dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 107 publications
1
107
0
Order By: Relevance
“…As shown in Table S3, the predictions indicate little overlap between the GO pathways that are enriched among the predicted targets. Although uncommon, miRNAs with the same seed can in principle have different targeting preferences that are dictated by variations outside of the seed sequence (68). For example, the members of the miR-29 family share the same seed sequence but display differences in the predicted targetomes: miR-29b localizes predominantly in the nucleus whereas miR-29a and miR-29c do not (69).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table S3, the predictions indicate little overlap between the GO pathways that are enriched among the predicted targets. Although uncommon, miRNAs with the same seed can in principle have different targeting preferences that are dictated by variations outside of the seed sequence (68). For example, the members of the miR-29 family share the same seed sequence but display differences in the predicted targetomes: miR-29b localizes predominantly in the nucleus whereas miR-29a and miR-29c do not (69).…”
Section: Discussionmentioning
confidence: 99%
“…A structurally accessible and evolutionarily conserved region (~10 nucleotides in length) was identified that alone can accurately predict AGO-mRNA associations, independent of the presence of miRNA binding sites . In any case, the impact of non-canonical targeting regarding target downregulation is not fully resolved (Khorshid et al, 2013;Martin et al, 2014;Wang, 2014). …”
Section: Non-canonical -Non-seed Interactionsmentioning
confidence: 99%
“…These three regions are in close proximity to each other, which was not found in the PR8 NS1 gene. It has been reported in a number of studies that miRNA can interact with the target mRNA in an imperfect seed-binding manner, albeit less frequently (Chi et al, 2012;Grimson et al, 2007;Martin et al, 2014). This might explain the inhibitory effect of the non-silencing shRNAmir on SIV/SK02 replication.…”
Section: Discussionmentioning
confidence: 93%